Peristaltic Motion of Carreau Fluid in a Channel with Convective Boundary Conditions - T. Hayat; Humaira Yasmin; A. Alsaedi (Applied Bionics and Biomechanics)
We investigate the peristaltic motion of Carreau fluid in an asymmetric channel with convective boundary conditions. Mathematical formulation is first reduced in a wave frame of reference and then solutions are constructed by long wavelength and low Reynolds number conventions. Results of the stream function, axial pressure gradient, temperature and pressure rise over a wavelength are obtained for small Weissenberg number. Velocity and temperature distributions are analyzed for different parameters of interest. A comparative study between the results of Newtonian and Carreau fluids is given.